Application Of Contextual Methods To Improve Short Writing Ability For Class Ix Students Of Junior High School - Sembiring, Anggi Shavira (Edumaniora : Jurnal Pendidikan dan Humaniora, 2022)
Writing is an activity to express thoughts, ideas or opinions and solve problems through written language media. Short stories are works of fiction that are fictitious, narrative or short storytelling (the storyline is solid while the background and flashbacks are included in passing). Because of its short form, short stories demand a concise narrative, not specific details that are "less important" and are more protracted. The purpose of this study was to improve the ability to write short stories through students' contextual methods. The research method used in this research is the classroom action research method. Data collection techniques were carried out by giving tests, observations and documentation. The data analysis techniques used are: 1) Test data analysis 2) Observation Result Data (Observation) Documentation Result Data 3) Documentation Result Data, The data source of this research is the making of this student short story which will be the main study of the author. The results of this study concluded that there were 7 students who completed the first cycle and 25 students who completed the second cycle, the application of contextual methods to students' short story writing contains many benefits for readers by animating the students' writing spirit.